2017
DOI: 10.20431/2454-6224.0301003
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Yield Potential and Herbage Quality of Alfalfa (Medicago Sativa L.) Genotypes in the Central Highland of Ethiopia

Abstract: /ha), Magna 801-FG(F) (6.2 t/ha), Magna 788 (5.6 t/ha) and FG-9-09 (F) (5.5 t/ha) genotypes. Similarly, hairy peruvian, FG-10-09 (F), Magna 801 FG (F), Magna 788 and FG-9-09(F) genotypes produced 77.7, 60.1, 55.6, 53.3 and 52.7cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In this regard, the present study showed consistency in plant height for genotype FGI-8091 followed by FGI-3054 and FGI-0916. Genetic variation among genotypes in the trial, response of genotypes to environmental factors and their interactions could be major reasons for the variation of plant height in the current study, and it was previously reported for different genotypes of alfalfa in which the current average result lay in the range (Kebede et al, 2017;Wayu & Atsbha, 2019). Selection of better yielding genotypes in one environment may not enable identification of genotypes that can repeat nearly similar performance in other environments (Kebede et al, 2017).…”
Section: Plant Height and Forage Yield At Harvestmentioning
confidence: 72%
See 2 more Smart Citations
“…In this regard, the present study showed consistency in plant height for genotype FGI-8091 followed by FGI-3054 and FGI-0916. Genetic variation among genotypes in the trial, response of genotypes to environmental factors and their interactions could be major reasons for the variation of plant height in the current study, and it was previously reported for different genotypes of alfalfa in which the current average result lay in the range (Kebede et al, 2017;Wayu & Atsbha, 2019). Selection of better yielding genotypes in one environment may not enable identification of genotypes that can repeat nearly similar performance in other environments (Kebede et al, 2017).…”
Section: Plant Height and Forage Yield At Harvestmentioning
confidence: 72%
“…RFV reveals the potential intake and fiber digestibility of legumes (Undersander & Moore, 2002) and reflects how well an animal will eat and digest a particular forage species when it is fed as the only source of energy (Kazemi et al, 2012). The RFV index observed for the cultivars evaluated was higher than a threshold level (RFV = 151) (Redfearn & Zhang, 2011) and by far better than the result reported before (Gashaw et al, 2015;Geleti et al, 2014;Kebede et al, 2017). Animal feed with a higher RFV index of more than 100 is considered to be a higher quality feed.…”
Section: Plant Height and Forage Yield At Harvestmentioning
confidence: 82%
See 1 more Smart Citation